PENGARUH PERBEDAAN PENGGUNAAN UMPAN TERHADAP HASIL TANGKAPAN IKAN CAKALANG (KASTSUWONUS PELAMIS) PADA ALAT TANGKAP HUHATE DI PERAIRAN TERNATE MALUKU UTARA - Susanto, Eko; Boesono, Herry; Fitri, Aristi (Journal of Fisheries Resources Utilization Management and Technology, 2012)
The mainly target of the operational of pole and line is skipjack tuna. Pole and line is a type of fishing gear that consist of pole, line and hook. The purpose of this research were to analyze the effect of artificial bait’s colours against total catch, to analyze the effect of type of live bait against total catch, and to analyze the interaction between the colours of artificial bait and live bait against total catch. The research was done in March-April 2012 in PPI Dufa-dufa Ternate. The research was used experimental fishing methods which have two variables they are: the color of artificial bait and live bait with 4 types of treatment. Normality test and ANOVA test by SPSS 16.0 was employed to analyze data.. The results of this research showed that the difference colours of artificial bait and live bait was effected the total catch of skipjack tuna it was seen from the total catch of anchovy artificial red bait as much as 544, and the total catch of anchovy artificial green bait fish as much as 329, the total catch of scad mackerel artificial red bait as much as 425 and the total catch of scad mackerel artificial green bait as much as 272. ANOVA test results showed that using pole and line with anchovy live bait and artificial red bait is better to be used.